2019
DOI: 10.3390/en12112164
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characterization of a Heat Management Module Containing Microencapsulated Phase Change Material

Abstract: In this study, a heat management module containing a microencapsulated phase change material (mPCM) was fabricated from mPCM (core material: paraffin; melting temperature: 37 °C) and aluminum honeycomb structures (8 mm core cell). The aluminum honeycomb functioned both as structural support and as a heat transfer channel. The thermal management performance of the proposed module under constant-temperature boundary conditions was investigated experimentally. The thermal protection period of the module decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A honeycomb sample (10 cm × 10 cm × 2.54 cm, core cell 8 mm) was tested experimentally in terms of thermal performance in PV panels providing sufficient heat conduction enhancement and unifying the interior temperatures of the module with no thermal stratification [ 19 ]. A subsequent study on mPCMs by similar authors confirmed the benefit of Al honeycomb working as a structural support and heat transfer channel facilitating thermal energy dissipation [ 20 ]. Another study reported an investigation of the effect of honeycomb core on latent heat storage (LHS) in PCM solar air heater (SAH).…”
Section: Introductionmentioning
confidence: 88%
“…A honeycomb sample (10 cm × 10 cm × 2.54 cm, core cell 8 mm) was tested experimentally in terms of thermal performance in PV panels providing sufficient heat conduction enhancement and unifying the interior temperatures of the module with no thermal stratification [ 19 ]. A subsequent study on mPCMs by similar authors confirmed the benefit of Al honeycomb working as a structural support and heat transfer channel facilitating thermal energy dissipation [ 20 ]. Another study reported an investigation of the effect of honeycomb core on latent heat storage (LHS) in PCM solar air heater (SAH).…”
Section: Introductionmentioning
confidence: 88%